Requirements of Energy and Protein for Arabic Chicken During Early Egg Production - Syafwan,; Noferdiman, (Tropical Animal Science Journal, 2020)
The objectives of this experiment were to calculate energy (ME) and crude protein (CP) requirements of Arabic chicken hens in the tropical climates during the early laying period by a choice feeding method. One hundred and thirty-eight of 22-week old Arabic chicken hens were allotted into 12 sheltered pens with 10-14 chicks each. The no free-choice group hens fed a standard diet conforming with the Hy-line Brown Commercial Management Guide, whilst the free-choice group hens fed with a standard diet, an energy-protein rich diet, an energy-rich diet, a protein-rich diet, and an energy-protein poor diet. Feed consumption, energy and protein consumptions, energy (kcal of ME/kg) and protein (g of CP/kg) dietary concentrations were recorded weekly, and egg production was recorded daily. All performance data were taken repeatedly during the first 28 weeks of egg production and were analyzed after summarizing weekly data into seven 28-d periods using the Mixed Procedure in SAS. The dietary treatments had no clear effect on feed and protein consumption but had a significant effect on energy consumption, energy and protein concentrations, and egg production. Energy consumption of the no free-choice group hens was lower than those in the free-choice group hens (1580 vs. 1718 kcal of ME/kg/hen; p